Karakteristik Fisik Bubuk Kopi Arabika Hasil Penggilingan Mekanis dengan Penambahan Jagung dan Beras Ketan - Hendri Syah; Yusmanizar Yusmanizar; Oki Maulana (Jurnal Teknologi dan Industri Pertanian Indonesia, 2013)
Size reduction applied on Arabica Coffee bean may change its physical properties, where these properties are utilized for designing process including packaging and appliances for further processes. This research aims to investigate physical characteristics of Arabica coffee powder with addition of corn and rice milled through mechanical process. This experiment used two mechanical mills including hammer mill and disc mill. Before it is milled, coffee was mixed with other materials including corn and rice. Parameters observed were yield, moisture content, bulk density, and angle of respose, particle uniformity index, fineness modulus, and the average particle dimensions. Based on the results obtained, it was revealed that moisture content of each test still meet SNI standard with the maximum of 7%. Bulk density of coffee powder resulted using disc mill was higher compared with hammer mill. However, particle generated from milling process may be categorized as powder with medium cohesiveness based on its angle of repose. Dimensional average particle is proportional to the fineness modulus of coffee powder produced. Highest fineness modulus obtained from coffee powder without additives, and using a hammer mill is equal to 4.37 with the highest average dimensions of 2.05 mm, while the lowest fineness modulus that the coffee powder without any additional ingredients milled with a hammer mill is equal to 4.22, with the lowest average dimensions of 1.94 mm.